Strategy to Increase Tourist Visit Interest in See Hin Kiong Temple to Empower the Economy of Padang City - Ibnu Muzaf; Rahmad Ramadan (Jurnal Dialektika: Jurnal Ilmu Sosial, 2025)
This study analyzes strategies that can be implemented to increase interest in visiting See Hin Kiong Temple to empower the regional economy of Padang City. Padang is the capital of West Sumatra Province which has a rich culture, one of which is See Hin Kiong Temple as a religious and Chinese cultural tourism destination that is a form of acculturation in Padang City. The purpose of this study is to determine the characteristics of See Hin Kiong Temple such as tourist attractions, facilities and infrastructure, transportation, tourism promotion, tourism management and develop strategies to increase interest in tourist visits to support the economic empowerment of Padang City. The method used is a qualitative descriptive analytical approach with direct observation, interviews with managers, and relevant literature studies to identify attractions, facilities and infrastructure, and economic potential in the Temple. The results show that See Hin Kiong Temple has the potential as a cultural heritage that encourages economic growth in Padang with characteristics such as advantages and disadvantages. See Hin Kiong Temple has historical and cultural value, architectural uniqueness equipped with a museum, a strategic location and cultural status. However, the Temple requires special maintenance making it difficult to preserve the building. Currently, the Temple is also less attractive to visit by the younger generation. The proposed strategies include creating structured tour packages with historical guidebooks, empowering local community human resources through management education, collaborating with the government and businesses for additional facilities, and digital promotion via social media and annual events.